An additional brain endocast of the ictidosaur Riograndia guaibensis (Eucynodontia: Probainognathia): intraspecific variation of endocranial traits - KERBER,LEONARDO (2021)
Abstract Recently, the morphology and encephalization of the brain endocast of the Triassic non-mammaliaform probainognathian cynodont Riograndia guaibensis were studied. Here, we analyzed the brain endocast of an additional specimen of this species. The new endocast shows well-defined olfactory bulbs and a median sulcus dividing the hemispheres, traits that were not clearly observed in the first studied specimen. Encephalization quotients were also calculated, revealing similar values to other non-mammaliaform cynodonts and lower than those of the first analyzed specimen. The analyzed cranium is slightly larger than the first studied one and may represent an advanced ontogenetic stage. Hence, these differences may be related to the intraspecific variation of this cynodont or alternatively, to the preservation of each specimen.